Synopsis of Senecio series Culcitium (Asteraceae: Senecioneae, Senecioninae) in the Andean region of South America - Salomón, Luciana; Sklenář, Petr; Freire, Susana E. (Phytotaxa, 2018)
Based on a detailed study of morphology and a critical analysis of species limits, we present a synopsis of Senecio ser. Culcitium from Andean South America. In this synopsis, Senecio ser. Culcitium is circumscribed including Aetheolaena and Lasiocephalus, two genera which are nested within Senecio. Forty three species are recognized in S. ser. Culcitium that are either rosette or scapiform herbs or subshrubs (sometimes scandent) bearing usually entire leaves, discoid and nodding capitula usually with conspicuous calycular bracts, penicillate style arms with or without a tuft of long hairs, and microechinate pollen. The new combination Senecio hyoseridis is proposed. The following names are proposed as synonyms: Senecio comosus var. debilis and S. comosus var. blancus with S. comosus; Senecio cuencanus var. tomentella with S. cuencanus; Senecio decolor, S. iscoensis and S. rosanus with Senecio antisanae, Senecio eliseae with S. rhizomatus; Senecio hypsobates var. parvulus with S. hypsobates; Senecio mochensis with S. pindilicensis; Senecio modestus with S. candollei; Senecio neeanus and S. haenkeanus with S. nivalis; Senecio quitensis with S. superandinus; Senecio santanderensis with S. cocuyanus; Senecio yacuanquensis with S. otophorus; Senecio zoellneri with S. keshua. Ten species previously placed in Senecio ser. Culcitium, i.e., S. aspleniifolius, S. candidans, S. comosus, S. diemii, S. gilliesii, S. jarae, S. julianus, S. magellanicus S. martinensis and S. stylotrichus, are excluded. Two of them, Senecio gilliesii and S. candidans are placed within Senecio ser. Hualtatini mainly by their herbaceous habit, stems usually leafy up to the apex, and erect capitula. Senecio jarae and S. aspleniifolius are placed in a new series based on the previously described Senecio sect. Repentes because of their solitary erect capitula and entire or deeply lobed leaves. Lectotypes are designated for 13 names. Additionally, 11 new illustrations, distribution maps, and identification keys are presented.